Implementasi Total Quality Management dan Pengaruhnya Terhadap Kualitas Produk - Risna Haryati; Dini Sudayanti (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The implementation of Total Quality Management and its effect on product quality, at PT QRS is the aim of research using this quantitative method, using primary data and secondary data which are processed using quantitative descriptive research methods. Primary data was obtained through direct observation, interviews and questionnaires, and secondary data from various literary sources, scientific books, internet sources, journals and various articles. The population of this study were employees in the Final Inspecting section, with a sample of 88 people. Questionnaires as primary data were then analyzed with validity tests, reliability tests, simple linear regression analysis, classical assumption tests, analysis of the coefficient of determination, and hypothesis testing using the t test and f test, which were processed with the help of the SPSS24 application. The results show that the implementation of Total Quality Management has a significant effect on the quality of PT QRS products.